Removing Malachite Green and Leucomalachite Green From Freshwater and Seawater With Four Water Treatment Agents - Lin, Yu-Ru; Hu, Yeh-Fang; Huang, Chih-Yang; Huang, Huai-Ting; Liao, Zhen-Hao; Lee, An-Ting; Wu, Yu-Sheng; Nan, Fan-Hua (Frontiers in Environmental Science, 2022)
Malachite green (MG) residue in aquatic environments can adversely affect food chains. To solve this problem, many adsorbents have been developed to remove MG from aqueous solutions. These adsorbents exhibit benefits in different aspects such as low cost, nontoxicity, and environment friendliness. Zeolite, oyster shell powder (OSP), humic acid (HA), and Chloride dioxide (ClO2) are widely used agents for water purification, indicating their potential to remove MG from both freshwater and seawater. Liquid chromatography tandem mass spectrometry was performed as a valid analytical method for measuring MG and its metabolite leucomalachite green (LMG). The analysis examined linearity, specificity, accuracy, precision, and limit of quantification. We found that three agents—zeolite, OSP, and HA—have high affinity for MG and LMG in both freshwater and seawater because of their physicochemical properties; ClO2 exhibited even greater efficiency for MG and LMG degradation due to its oxidation capacity. The MG removal efficiency of zeolite, OSP and HA in freshwater was 100%, 87.52%, and 100%, respectively. In the MG-containing seawater, the removal efficiency of zeolite, OSP and HA was 95.24%, 6.57%, and 89.36%, respectively. The LMG removal efficiency of zeolite, OSP and HA in freshwater was 100%, 53.56%, and 100%, while in seawater, the LMG removal efficiency of zeolite, OSP and HA was 100%, 62.70%, and 84.65%, respectively. ClO2 treatments in both freshwater and seawater expressed 100% removal efficiency. The adsorption capacity of three water agents in MG-containing freshwater decreased in the order: zeolite = HA > OSP; in MG-containing seawater: zeolite > HA > OSP. Whereas the adsorption capacity of three water agents in LMG-containing freshwater decreased in the order: zeolite = HA > OSP; in LMG-containing seawater: zeolite > HA > OSP. In this study, four water treatment agents are reported to remove MG and LMG from freshwater and seawater, indicating their potential for reducing the amount of hazardous MG and LMG residue in aquatic environments.